(untitled) (Islamic Sciences Journal, 2025)
This research aims to introduce Imam Ibn Rushd al-Jadd (the Grandfather) and his book Al-Muqaddimat al-Mumahhidat. Imam Ibn Rushd al-Jadd is one of the prominent scholars of the Maliki school of jurisprudence, yet his contributions and methodology remain unfamiliar to many students and researchers. His approach to legal reasoning, evidence-based analysis, and preference for certain rulings in his works are often overlooked. This necessitates a concise scholarly study to highlight his significance and elucidate the methodology he employed in Al-Muqaddimat al-Mumahhidat, which addresses the legal rulings and foundational principles derived from Al-Mudawwana (a key Maliki legal text). The first section of this research focuses on introducing Imam Ibn Rushd al-Jadd and his book, explaining its role in clarifying complex legal issues. The second section examines his methodology in deriving rulings from the Sunnah, the second primary source of Islamic jurisprudence. It defines the Sunnah linguistically and terminologically, discusses its position among Islamic legal sources, and demonstrates how Imam Ibn Rushd al-Jadd relied on authentic hadiths and narrations to construct legal arguments. The research also highlights his ability to interpret ambiguous hadiths, distinguish between authentic and weak narrations, and articulate their legal implications. This deep engagement with the Sunnah underscores his expertise and establishes his book as an indispensable reference for jurists and students alike, solidifying its status as a cornerstone of Maliki and Islamic jurisprudence